Molecular approaches to the identification of DNA markers for drug resistance in Trypanosoma congolense - Majiwa, Phelix A.O.; Konde, V.; Souza, M. de; Peregrine, A.S.; Maina, M. (European Union, 2000)
Trypanosomosis remains one of the biggest impediments to the Development of the livestock industry in sub-Saharan Africa while it is likely that a vaccine for this disease could be found in the future, none is presently available. Mean-while different strategies are being followed to control this disease. Among the control options, drug therapy and prophylaxis are the ones most broadly used for controlling the disease in many countries of Africa. Unfortunately, the utility and efficacy of these drugs are being seriously undermined by the emergence and spread of drug resistant trypanosomes, instances of trypanosomes resistant to these drugs. This paper discusses the molecular approaches to the identification of DNA markers for drug resistance in Trypanosoma congolense.